Optimization of Traffic Violation Enforcement Through Mobile ETLE by Pekalongan Police Satlantas in Order to Realize Kamseltibcarlantas - Evran (Advances in Police Science Research Journal, 2024)
There are frequent traffic violations leading to a high number of traffic accidents within the jurisdiction of the Pekalongan Police Resort. ETLE Mobile is an advanced system that is expected to realize safe and orderly traffic, but the use of ETLE Mobile is said to be suboptimal for the enforcement of traffic violations in the jurisdiction of the Pekalongan Police Resort. This study aims to describe the implementation of traffic violation enforcement carried out by the Traffic Unit of the Pekalongan Police Resort through the use of ETLE Mobile and to optimize the use of ETLE Mobile to realize safe and orderly traffic in the jurisdiction of the Pekalongan Police Resort. The research method used in this study is a qualitative approach, with a case study research design. The research location is the Pekalongan Police Resort, which has been designated by the Police Academy. The data sources consist of primary data as the main data, as well as secondary data as complementary data. The data was collected through observations, interviews, and document analysis. The data was then validated through data and method triangulation. Data analysis was conducted qualitatively, which includes data reduction, data presentation, and conclusion/verification drawing, based on George R. Terry’s management theory as the analytical framework. The results of the study indicate that the optimization of the Traffic Unit of the Pekalongan Police Resort in enforcing traffic violations using ETLE Mobile in the Pekalongan Police Resort to reduce traffic violations still has shortcomings and limitations, such as the absence of activity plans, SOP regarding ETLE Mobile, and a shortage of personnel from the Traffic Unit of the Pekalongan Police Resort who have completed specialized and general education. Therefore, it is expected that the optimization of traffic violation enforcement can be achieved by creating an ETLE application to facilitate the public in knowing and confirming traffic violations.